COMPREHENSION LEVEL ANALYSIS OF REGIONAL GOVERNMENT AGENCIES AGAINST ACCRUAL BASED GOVERNMENT ACCOUNTING STANDARDS IN ACCORDANCE WITH PP NO. 71 2010 (A CASE STUDY OF LOCAL GOVERNMENT OF SUMENEP) - R Boby Tri Arganata; Lilik Purwanti (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2014)
The purpose of this research is to determine the level of understanding of local government of Sumenep officials in implementation of PP 71 2010 about concerning Governmental Accounting Standards (SAP) accrual-based and what factors become the obstacle. The type of this research is qualitative descriptive. The object of this research is the local government of Sumenep. Data used in this study are primary data and secondary data. The methods of data analysis using descriptive analysis. The results by using data analysis and research findings in local government officials of Sumenep that observed from parameters common understanding, structure’s understanding, and the implementation confirm that the local government officials of Sumenep has a good level of understanding and ready for implementing SAP 2010 accrual basis Untortunately, in the implementation of PP No. 71 2010 about Government Accounting Standards is still needs some improvement cause of Local Government Financial Report (LKPD) has been done manually (excel) and staff’s education who are not appropriate in department or expertise. Keywords : Standar Akuntansi Pemerintahan, Akrual Basis, Pemerintah Daerah